Effect of Health Education on COVID-19 Preventive Behaviors in Oil Industry Workers: An Application of Health Belief Model - Sahar Mohammadnabizadeh; Ali Asghar Najafpoor; Vahid Ghavami (Gonabad University of Medical Sciences, 2023)
Background: Recently, the pandemic of coronavirus disease 2019 (COVID-19) is a new emerging universal challenge in infectious epidemic disease management. Even today, with access to vaccines, the most effective intervention is behavioral intervention, and as new types emerge, it continues to be significant. The goal of the present study was to promote preventive behaviors during the coronavirus pandemic among oil factory workers using the health belief model (HBM). Methods: A total of 138 onshore shift workers (69 control and 69 case group) were randomly chosen from the two sites of oil fields in southern Iran. Data collection tools were demographic characteristics questionnaire, COVID-19 knowledge questionnaire, HBM questionnaire, and prevention behaviors questionnaire. The Whatsapp application was used to educate the intervention group. Workers completed questionnaires at baseline, after the intervention, and three months after the educational program. Data analyses were done using SPSS software, version 24. Results: Except for knowledge and cues to action, there were significant interactions between time and group for HBM constructs and behavior (P≤0.05). Furthermore, there were significant changes in all variables between follow-up and baseline in the intervention group (P≤0.05). The linear regression indicated that the perceived benefit (ß=0.48, P=0.001) and self-efficacy (ß=0.40, P=0.001) were the most effective factors in preventive behavior, respectively. Conclusion: The results showed that efficient education based on the HBM and emphasizing enhancing knowledge and preventive behavior adoption can prevent individuals from developing COVID-19 and its complications. Considering that the perceived benefits and self-efficacy were the strongest predictor of behavior, attention to these constructs in educational interventions, especially among oil factory shift workers studied, who are at risk of COVID-19 and without enough knowledge, can provide better outcomes related to COVID-19 preventive behaviors.